2008
DOI: 10.1016/j.jvs.2008.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Subintimal angioplasty: Our experience in the treatment of 506 infrainguinal arterial occlusions

Abstract: SIA is an effective percutaneous technique for the revascularization of patients with lower extremity chronic arterial occlusions involving the superficial femoral artery. The procedure is successfully performed in all segments of the lower extremity with minimal morbidity or mortality. Rates of limb salvage and improvement in claudication are similar to those achieved by open surgical bypass, while modest reductions in limb salvage and primary patency are experienced in limbs with femorotibial occlusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 34 publications
0
27
0
2
Order By: Relevance
“…In the study by Treiman et al, routine full-lesion stenting after SIA resulted in poor vessel patency, e.g., as low as 18% after 3 years [13]. In contrast, Scott et al showed improved long-term primary patency rates using selective stenting, approximately 45% to 55% at 1 year and approximately 25% at 3 years [20,21]. In our series, by using stenting selectively as bail-out strategy, cumulative proportional primary patency was calculated at 80.1%, 42.3%, and 29.0% at 12, 24, and 36 months, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…In the study by Treiman et al, routine full-lesion stenting after SIA resulted in poor vessel patency, e.g., as low as 18% after 3 years [13]. In contrast, Scott et al showed improved long-term primary patency rates using selective stenting, approximately 45% to 55% at 1 year and approximately 25% at 3 years [20,21]. In our series, by using stenting selectively as bail-out strategy, cumulative proportional primary patency was calculated at 80.1%, 42.3%, and 29.0% at 12, 24, and 36 months, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…However, the risk of arterial perforation may be higher in EVT with subintimal stent placement than that with intraintimal stent implantation because crural arteries are more fragile. Previous studies have reported the incidence of arterial perforation after subintimal stent placement following occluded lesions in the SFA to range from 2% to 3% [8,9]. In our case, the pseudoaneurysm developed probably due to arterial rupture caused by subintimal stent placement in the SFA.…”
Section: Discussionmentioning
confidence: 47%
“…Prior reports suggest inferior primary and secondary patency with percutaneous revascularization for critical limb ischemia compared to claudication. 7,8 However, these case series are limited by smaller numbers of patients with a mixture of iliac and infra-inguinal disease, 7 and/or shorter (12 months) follow-up. 7,8 Our results suggest that the biological response to percutaneous treatments is similar between the two groups and supports increasing trends to endovascular treatment as a first-line therapy for critical limb ischemia.…”
Section: Patency After Revascularizationmentioning
confidence: 99%